Two-body problems in the orthogonal condition model - M, M.Odsuren; G.Khuukhenkhuu; S.Davaa; K.Katō; A. Sarsembayeva (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this work we investigate the 0+, 2+, 4+, 6+, 8+ and 10+resonant states of the + system and each advantage of Gaussian and Harmonic Oscillator basis wave functions in the complex scaled orthogonal condition model (CSOCM).